Rancang Bangun Buck-Boost Converter menggunakan Kendali PID - Sheren Diusti Dwi Putri; Aswardi Aswardi (Universitas Negeri Padang, 2020)
AbstractThis paper discusses the Buck-Boost converter Design Using PID Control. Buck-Boost converter is a type of DC-DC converter that can convert DC voltage to a higher level or lower level. The buck-boost converter uses the PID system which is expected to produce a Buck-Boost converter output voltage in accordance with the setpoint and get a stable output voltage response, without overshooting and fast rise time. Tuning of PID parameters is done by the modified Ziegler Nichols 2 method, namely the original ZN, some overshoot, and No overshoot. Of the 3 types of tuning the PID has not gotten results in accordance with the design objectives, while it is still a high error and an unstable response. So the trial and error methods is used to get optimal results with PID parameters, namely Kp = 0.34, Ki = 0.350 and Kd = 0.019. The PID tuning of the trial and error method results in a stable response with steady-state error = 0, time delay = 0.37 s, rise time = 1.8 s, peak time = 0 and settling time = 1.8 s. From the results of the Buck-Boost converter output response proved the Buck-Boost converter using PID control was in accordance with the design goals.